Grass-like mantid, American grass mantid, Thesprotia graminis, (Scudder, 1878) (Insecta: Mantodea: Thespidae) - Bethany McGregor; Nathan Burkett-Cadena; Andrea Lucky (EDIS)
Praying mantids are charismatic insects that are considered beneficial to humans because of their insectivorous lifestyle and because of their aesthetic appeal. Despite this, many praying mantid species remain understudied. One species that occurs in the southeastern United States is the grass-like mantid, Thesprotia graminis (Scudder) (Figure 1). This small, cryptic mantid species is light brown to green in color and can easily blend in with pine needles and grass, making it difficult to detect in its natural habitat.